2020
DOI: 10.1172/jci133982
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific repression of AMPKα1 alleviates pathophysiology in Alzheimer’s model mice

Abstract: Figure 1. Expression of AMPKα isoforms is dysregulated in AD hippocampus. (A) Hippocampus (Hip) lysate from sAD patients showed increased AMPKα1 and decreased AMPKα2 levels as compared with those of age-matched controls (CT). n = 10 with up to 4 technical replicates. *P = 0.0119; **P = 0.0014, unpaired t test. (B) Representative images of AMPKα isoform dysregulation in area CA1 of hippocampus in AD and age-matched control patients. Scale bar: 50 μm. Immunohistochemical experiments were replicated independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 69 publications
(106 reference statements)
5
42
0
1
Order By: Relevance
“…Second, similar to the results from hippocampus, most altered proteins in PFC are uniquely regulated by suppression of either AMPKα1 or α2 (but not both). The results are consistent with recent studies indicating isoform-specific roles of AMPKα in neuronal plasticity, cognitive function, and neurodegenerative diseases(Yang et al, 2020;Zimmermann et al, 2020). As discussed above, AMPK plays a central role in regulating cellular energy homeostasis, disruption of which is indicated many…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Second, similar to the results from hippocampus, most altered proteins in PFC are uniquely regulated by suppression of either AMPKα1 or α2 (but not both). The results are consistent with recent studies indicating isoform-specific roles of AMPKα in neuronal plasticity, cognitive function, and neurodegenerative diseases(Yang et al, 2020;Zimmermann et al, 2020). As discussed above, AMPK plays a central role in regulating cellular energy homeostasis, disruption of which is indicated many…”
supporting
confidence: 93%
“…Notably, one of the top proteins that were uniquely upregulated in hippocampi of the AMPKα1 cKO mice is NEDD8-activating enzyme E1 regulatory subunit (Q8VBW6), which can bind to the amyloid precursor protein and is considered to play a role in AD pathogenesis (Chen, McPhie, Hirschberg, & Neve, 2000;Gong & Yeh, 1999). Such finding is interesting in light of our recent studies suggesting a critical role of AMPKα1 dysregulation in AD pathophysiology (Zimmermann et al, 2020). It is also worth mentioning another upregulated protein in the AMPKα1 cKO condition: Polyadenylate-binding protein 1 (PABP1, P29341).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, prior studies demonstrated AMPK activation, measured by Thr172 phosphorylation, in cerebral neurons of multiple tauopathies, including Pick's disease and progressive supranuclear palsy (6). Since Zimmermann et al (17) did not determine AMPK activation/phosphorylation in the human brain, there is a possibility that phosphorylation, rather than expressional change, may activate AMPK in FTD or DLB samples. Nevertheless, the isoform-specific dysregulation of AMPK in postmortem AD brain tissue raised the important question of how AMP-Kα1/2 is differentially regulated in AD.…”
Section: Ampk Isoform Differences In Alzheimer's Diseasementioning
confidence: 99%
“…The AMPK is a serine/threonine kinase with a key role as an energy sensor in a wide variety of tissues. It coordinates cell growth, autophagy, and metabolism [ 48 , 49 , 50 , 51 ], and appears to be involved in the pathophysiology of AD [ 52 ]. AMPK is a trimer, with α-, β-, and γ-subunits.…”
Section: Introductionmentioning
confidence: 99%